The burning of the Lakshagriha (house of lacquer) with the Pandavs trapped inside. In the Mahabharat, Duryodhana planned to eliminate the Pandav brothers by inviting them to the palace made of lacquer. The panel shows the flames erupting from the house with the Pandavs inside. - Brig. Ajai Singh (2021)
Image courtesy: Brig A.P. Singh - www.collectingmoments.in